TSLP bronchoalveolar lavage levels at baseline are linked to clinical disease severity and reduced lung function in children with asthma - Chorvinsky, Elizabeth; Nino, Gustavo; Salka, Kyle; Gaviria, Susana; Gutierrez, Maria J.; Pillai, Dinesh K. (Frontiers in Pediatrics, 2022)
Rationale: Thymic stromal lymphopoietin (TSLP) is increasingly recognized as a key molecule in asthma pathogenesis and as a promising therapeutic target in adults. In contrast, in asthmatic children the clinical relevance of TSLP secretion in the lower airways has been remarkably understudied. We tested the hypothesis that pulmonary TSLP levels in asthmatic children correlate with clinical severity, airway inflammation and lower airway obstruction. Methods: Bronchoalveolar lavage (BAL) samples and relevant clinical data were collected from asthmatic children undergoing clinically indicated bronchoscopy at Children's National Hospital in Washington D.C. Protein levels of TSLP, IL-5, IL-1β, and IL-33 were quantified in BAL at baseline and correlated with individual severity and clinical features including spirometry, serum IgE and eosinophils, BAL neutrophil and eosinophil counts. Results: We enrolled a total of 35 asthmatic children (median age: 9 years). Pediatric subjects with severe asthma had greater TSLP BAL levels at baseline relative to mild or moderate asthmatic subjects (p=0.016). Asthmatic children with the highest TSLP levels (>75th percentile) had higher IL-5 and IL-1β BAL levels and greater lower airway obstruction (lower FEV1/FVC ratios). Conclusion: Our study demonstrates for the first time that higher pulmonary TSLP levels obtained at baseline are linked to asthma disease severity in a subset of children. These data indicate that TSLP may play a key role in the pathogenesis of pediatric asthma and thus provide initial support to investigate the potential use of anti-TSLP biologics to treat severe uncontrolled asthmatic children.